2018
DOI: 10.1016/j.jshs.2017.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 26-month floorball training on male elderly's cardiovascular fitness, glucose control, body composition, and functional capacity

Abstract: BackgroundFloorball training offers a motivating and socially stimulating team activity for older adults, and 12 weeks of floorball training twice a week among men aged 65–76 years have been shown to have positive effects on a number of physiological parameters important for health. However, the effect of long-term participation in floorball training among male elderly has not been investigated. The aim of the present study was to examine the effect of 26-month self-organized regular participation in floorball… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 41 publications
2
18
0
3
Order By: Relevance
“…Chekroud et al 1 show that the correlation with mental health burden was lowest when individuals engage in about 45 min of exercise 3–5 days per week. This is in close agreement with the recommendation of 150 min per week of moderate-to-vigorous physical activity from the World Health Organization and also aligns with numerous recent training studies showing that marked fitness and positive physiological health effects result when individuals exercise 2–3 times per week for 60 min or participate in a team sport 3 times per week for 40 min 9, 10, 11. This inverted U relationship corroborates findings showing that excessive exercising is often related to mental health problems (e.g., exercise addiction 12 ) and simultaneously indicates that only a sufficient frequency and volume of physical exercise is related to fewer days of mental ill-being.…”
supporting
confidence: 91%
“…Chekroud et al 1 show that the correlation with mental health burden was lowest when individuals engage in about 45 min of exercise 3–5 days per week. This is in close agreement with the recommendation of 150 min per week of moderate-to-vigorous physical activity from the World Health Organization and also aligns with numerous recent training studies showing that marked fitness and positive physiological health effects result when individuals exercise 2–3 times per week for 60 min or participate in a team sport 3 times per week for 40 min 9, 10, 11. This inverted U relationship corroborates findings showing that excessive exercising is often related to mental health problems (e.g., exercise addiction 12 ) and simultaneously indicates that only a sufficient frequency and volume of physical exercise is related to fewer days of mental ill-being.…”
supporting
confidence: 91%
“…Given that many are experiencing stressful life challenges under the COVID-19 pandemic crisis, it is imperative to develop innovative and effective PA intervention programs that reduce stress and promote health and wellbeing in older adults [12,13]. One innovative intervention strategy that has shown promise in the healthcare field is virtual reality (VR)-based PA interventions [14].…”
Section: Introductionmentioning
confidence: 99%
“…Work to date indicates that sport participation as a health promotion activity has a broad spectrum of physical and psychological benefits in not only healthy/asymptomatic individuals but also clinical populations with common cardiometabolic comorbidities including hypertension, diabetes, and obesity regardless of age, sex, and socioeconomic background. A summary of beneficial effects resulting from a period of participation in individual and team-based sport activities including golf, 42 rugby, 54,55 soccer, [56][57][58][59][60] basketball, 61 handball, 62 and floorball 63,64 in untrained, healthy/ asymptomatic individuals and noncancer patients is presented in Table 1. Likewise, a small but growing number of studies [65][66][67][68][69][70][71][72][73][74][75][76][77][78][79] have shown that regular participation in individual and team-based sports (including triathlon, wall climbing, dragon boat racing, and soccer) is also effective as an exercise therapy for persons previously diagnosed with cancer (mostly breast and prostate cancer) in alleviating diseaserelated and treatment-related adverse effects on physical, physiological, and psychological function (Tables 2 and 3).…”
Section: Sport and Cancer Managementmentioning
confidence: 99%